Legal Politics of Ex-Convicts in Contesting Regional Head Elections - Adi Purnomo Santoso; Zainal Arifin Hoesein (Yayasan Adra Karima Hubbi, 2024)
The regulation of ex-convicts’ political rights in legislative and executive elections has historically prohibited those sentenced to five years or more imprisonment from running for office. This legal framework has undergone significant changes following the Constitutional Court Decision Number 42/PUU-XIII/2015. To analyze the legal politics surrounding ex-convicts’ participation in regional head elections and examine the implications of the Constitutional Court’s decision on their political rights. This study employs a normative legal research methodology, analyzing relevant legislation, Constitutional Court decisions, and public response to changes in electoral regulations regarding ex-convicts’ participation. The Constitutional Court Decision Number 42/PUU-XIII/2015 declared the blanket ban on ex-convicts unconstitutional, allowing their participation provided they publicly disclose their status. This decision was subsequently incorporated into Law Number 7/2017 on Elections. However, significant public opposition to ex-convicts’ participation in elections persists despite these legal reforms. While legal reforms have expanded ex-convicts’ political rights through conditional participation in elections, there remains a notable disconnect between legal developments and public sentiment regarding ex-convicts’ electoral participation.